Market institutions: enhancing the value of rural-urban links - Chowdhury, Shyamal; Negassa, Asfaw; Torero, Máximo (International Food Policy Research Institute, 2005)
This paper examines how market institutions can affect links between urban and rural areas with specific emphasis on goods market integration in the national context. Traditionally, development researchers and practitioners have focused either on rural market development or on urban market development without considering the interdependencies and synergies between the two. However, more than ever before, emerging local and global patterns such as the modern food value-chain led by supermarkets and food processors, rapid urbanization, changes in dietary composition, and enhanced information and communication technologies point to the need to pay close attention to the role of markets both in linking rural areas with intermediate cities and market towns and promotion of economic development and poverty reduction. This paper begins with a presentation of a conceptual framework of market integration and then identifies five major factors that increase the transfer costs that subsequently hinder market integration between rural and urban areas: information asymmetry, transaction costs, transport and communication costs, policy induced barriers, and social and noneconomic factors. Five specific cases in five developing countries are examined in this study to demonstrate the primary sources of transfer costs and the aspects of market institutions that are important to market integration and promotion of rural-urban linkages.